2012
DOI: 10.1111/j.1464-410x.2012.11155.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative metastatic status, level of thrombus and body mass index predict overall survival in patients undergoing nephrectomy and inferior vena cava thrombectomy

Abstract: Study Type – Prognosis (case series) Level of Evidence 4 What's known on the subject? and What does the study add? Little is known about the prognostic impact of body mass index (BMI) and obesity on patients with locally advanced kidney cancer. Previous studies suggest that clinical/pathological stage, the proximal extent of the tumour thrombus, direct vascular wall invasion, and preoperative performance status may all constitute important prognostic factors within this patient population. The present study sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…Interestingly, higher BMI was associated with lower cancer mortality in several studies . It is important to note that the trend for better outcomes in patients with higher BMI is also evident in the present study, despite the technical challenges of nephrectomy with thrombectomy in patients with higher BMI. Preoperative haemoglobin level is also known to predict survival in patients with RCC after surgery or after diagnosis of metastatic disease , but anaemia has not been identified in previous studies evaluating RCC with venous invasion.…”
Section: Discussionsupporting
confidence: 69%
“…Interestingly, higher BMI was associated with lower cancer mortality in several studies . It is important to note that the trend for better outcomes in patients with higher BMI is also evident in the present study, despite the technical challenges of nephrectomy with thrombectomy in patients with higher BMI. Preoperative haemoglobin level is also known to predict survival in patients with RCC after surgery or after diagnosis of metastatic disease , but anaemia has not been identified in previous studies evaluating RCC with venous invasion.…”
Section: Discussionsupporting
confidence: 69%
“…The predictive role of level of tumor thrombus for oncologic outcomes is controversial. Previous published studies have reported adverse oncologic outcomes for patients with high‐level tumor thrombus, though there are also significant data proposing that IVC thrombus level is not a predictor of oncologic outcomes . The level of tumor thrombus is short of predictive significance in the present cohort.…”
Section: Discussioncontrasting
confidence: 52%
“…Previous published studies have confirmed that patients with RCC accompanying tumor thrombus and metastases at surgery experience remarkably poor OS when compared to those with non‐metastatic disease. Presence of distant metastasis was also demonstrated to be an independent prognostic factor in multivariate analysis . Tumor Fuhrman grade and maximum width were also common prognosis predictors in patients with RCC and VTT .…”
Section: Discussionmentioning
confidence: 83%
“…The median survival of the patients with papillary subtype was 5.2 months when those patients were positive for node or distant metastases. In general, node or distant metastases have been reported to be predictive factors for the poor prognosis . In addition, this extensive surgery is associated with a high mortality or morbidity rate.…”
Section: Discussionmentioning
confidence: 99%